2020
DOI: 10.1108/apjml-08-2019-0475
|View full text |Cite
|
Sign up to set email alerts
|

Integrative perceived values influencing consumers' attitude and behavioral responses toward mobile location-based advertising: an empirical study in Vietnam

Abstract: PurposeThe purpose of this paper is to examine a proposed model of location-based advertising (LBA) effectiveness upon the influence of integrative perceived values on consumers' attitude and behavioral responses in the immaturity of LBA in Vietnam.Design/methodology/approachA survey research method was utilized to collect data from mobile users. A real sample of 459 respondents was deemed and the Structural Equation Modeling (SEM) was applied to analyze data.FindingsThe results unveil that contextual offers, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
65
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(74 citation statements)
references
References 63 publications
5
65
4
Order By: Relevance
“…It serves as perceived usefulness of social media in their options. Previous literature studied its positive impact on loyalty (Sarkar and Sarkar, 2019) and favorable evaluation (Le and Wang, 2021). Al-Debei et al (2015) found that when information on websites fulfills consumer interests, they would reinforce credibility with creators.…”
Section: Conceptual Model and Hypotheses 231 Information Relevance (Rel)mentioning
confidence: 99%
“…It serves as perceived usefulness of social media in their options. Previous literature studied its positive impact on loyalty (Sarkar and Sarkar, 2019) and favorable evaluation (Le and Wang, 2021). Al-Debei et al (2015) found that when information on websites fulfills consumer interests, they would reinforce credibility with creators.…”
Section: Conceptual Model and Hypotheses 231 Information Relevance (Rel)mentioning
confidence: 99%
“…, 2021; Ghazali et al. , 2018; Le and Wang, 2020). It is vital to investigate the relative effectiveness of mobile channels so that sellers may take advantage of such knowledge when deciding on multi-channel advertising spending (Ghose et al.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…In summary, those studies do not suggest consistent advertising effectiveness on different devices (PC vs. mobile). Mobile devices have become the dominant channel for reaching consumers (Jain et al, 2021;Ghazali et al, 2018;Le and Wang, 2020). It is vital to investigate the relative effectiveness of mobile channels so that sellers may take advantage of such knowledge when deciding on multi-channel advertising spending (Ghose et al, 2013).…”
Section: The Advertising On Different Devicesmentioning
confidence: 99%
“…Later, credibility (Brackett and Carr, 2001), incentives (Kim and Han, 2014) and message relevance (Lin and Bautista, 2018) were proposed and added as antecedents that significantly influence advertising value (Lin and Bautista, 2018;Khasawneh and Shuhaiber, 2018). Recent studies (Aydin and Karamehmet, 2017;Lin and Bautista, 2018;Martins et al, 2019) Le and Wang (2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Entertainment, informativeness and irritation were suggested by Shareef et al (2019) as antecedents of perceived advertising value in the social media marketing context. In the field of location-based mobile advertising, the antecedents discovered include contextualization, relevance, entertainment, irritation and credibility by Lin and Bautista (2018), information, entertainment, credibility and irritation by Hakimi et al (2019), and incentives, trustworthiness, personalization, perceived enjoyment and perceived encroached risk by Le and Wang (2020).…”
Section: Literature Reviewmentioning
confidence: 99%